Sterols and Sterol Glucoside from Phyllanthus Species (Dhaka University Journal of Science, 2012)
Stigmasterol, stigmasta-5,22-dien-3-O-?-D-glucoside, ?-sitosterol, and sitosterol-3-O-?-D-glucoside were obtained from the organic solvent extractives of different parts of Phyllanthus species P. niruri, P. reticulatus, P. emblica, and P. acidus, through chromatographic separation. The structures of isolated compounds have been elucidated with the help of physical and spectroscopic studies. Medicinal importances of these species have also been discussed.DOI: http://dx.doi.org/10.3329/dujs.v60i1.10327Dhaka Univ. J. Sci. 60(1): 5-10, 2012 (January)